Field report: Iowa - Robinson, John C., 1959-et al (1985)
Field notes by John C. Robinson listing various birds he saw between May 15 and May 20, 1985. The field report includes a brief note to Thomas H. Kent about Robinson having enjoyed being in Iowa again. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1985. Epson - sheet feed/flatbed